Therapeutic use of selective synthetic ligands for retinoic acid receptors: a patent review. (2nd August 2016) - Marchwicka, Aleksandra; Cunningham, Alan; Marcinkowska, Ewa; Brown, Geoffrey
ABSTRACT: Introduction : Differentiation therapy using all- trans retinoic acid (ATRA) revolutionised the treatment of acute promyelocytic leukaemia to such an extent that it is now one of the most curable types of leukaemia, with ATRA and anthracycline-based chemotherapy providing cure rates above 80%. Isotretinoin is used to treat chronic acne. Here, we examine the information described in recent patents and the extent to which new findings are influencing extending retinoid-based differentiation therapy to other cancers, as well as the development of new therapies for other disorders. Areas covered : A search has been performed on the literature and worldwide patents filed during 2014 to the present time, focusing on synthetic agonists and antagonists of retinoic acid receptors and novel compositions for the delivery of these agents. Expert opinion : New potential therapeutic applications have been described, including lung, breast and head and neck cancers, T cell lymphoma and neurodegenerative, metabolic, ophthalmic, muscle, and inflammatory disorders. Recent patents have described the means to maximise retinoid activity. Two decades of efforts to extend retinoid-based therapies have been disappointing and new synthetic retinoids, target diseases and modes of delivery may well resolve this long standing issue.